2021
DOI: 10.3390/en14164909
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Heat Transfer in Fine Dispersive Slurry Flow

Abstract: Slurry flows commonly appear in the transport of minerals from a mine to the processing site or from the deep ocean to the surface level. The process of heat transfer in solid–liquid flow is especially important for the long pipeline distance. The paper is focused on the numerical modelling and simulation of heat transfer in a fine dispersive slurry, which exhibits yield stress and damping of turbulence. The Bingham rheological model and the apparent viscosity concept were applied. The physical model was formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The author concluded that for the same bulk velocity of the slurry, the Nusselt number decreases with an increase in solid volume concentration, and the highest rate of decrease in the Nusselt number is for a solid concentration below 10% by volume. The author noticed that more work needs to be done on examining the new Nusselt number for solid volume concentrations below 10% and greater than 30%, for different heat fluxes and pipe diameters [41].…”
Section: Review Of Contribution To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The author concluded that for the same bulk velocity of the slurry, the Nusselt number decreases with an increase in solid volume concentration, and the highest rate of decrease in the Nusselt number is for a solid concentration below 10% by volume. The author noticed that more work needs to be done on examining the new Nusselt number for solid volume concentrations below 10% and greater than 30%, for different heat fluxes and pipe diameters [41].…”
Section: Review Of Contribution To the Special Issuementioning
confidence: 99%
“…Passive methods, such as increasing heat transfer area and/or temperature difference, shaping an insert with dedicated perforation, or mechanically deformed pipes, have been studied for several years and have become commercial solutions [4][5][6][7][8][9]. Active methods, such as air injection, bubble or vortex generation, or proper pulsation, can lead to increased heat transfer coefficient, and, finally, can produce increased heat transfer process [10][11][12][13]. Some of such methods have been demonstrated by contributors to the Special Issue.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of increasing the viscosity at the wall was indirectly confirmed by Squires and Eaton (1990), who used direct numerical simulation of isotropic turbulence to investigate the effect of turbulence on the solid concentration of heavy particles. Some other researchers reasoned that a laminarisation effect in fine dispersive slurries exists (Wilson and Thomas, 1985), (Bartosik, 2008). In conclusion, slurry flow with fine solid particles is very complex, and it remains a challenge to perform experiments on the influence of the solid particles on the transition to turbulence.…”
Section: Introductionmentioning
confidence: 97%